Digitalizing employment services: infrastructure, competency, and cultural challenges of civil servants - Agustinus Fatem; Sabar Parlindungan Sormin; Yosephina Ohoiwutun; Septinus Saa (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
This study examines the challenges in the digitization of personnel services within the management system of the State Civil Apparatus in Keerom Regency. This study identifies several key barriers, including limited digital infrastructure, insufficient internet connectivity, a lack of technological devices, low competency among civil servants in utilizing information and communication technology, as well as cultural resistance to digital transformation. A descriptive qualitative approach is employed through the methods of field observation, in-depth interviews, and analysis of policy documents. The research findings indicate that the efforts for digitalization are not evenly distributed across all work units, as the digital system remains centralized in the main personnel unit, while the supporting units still rely on manual processes. Furthermore, the lack of standardized application processes and data results in low efficiency and accountability in services. This study presents strategic steps to address the identified issues, including the enhancement of infrastructure, the improvement of digital competencies among civil servants through ongoing training, and the encouragement of a workplace culture that embraces digital technology. The results of this study contribute to the development of a model for accelerating the digitalization of civil servants at the regional level to enhance the quality of public services that are responsive, integrated, and sustainable. The significance of this study lies in its localized focus on a 3T (frontier, outermost, underdeveloped) region, providing a nuanced understanding of digital transformation challenges often overlooked in centralized policy-making.